PENGARUH MODEL PEMBELAJARAN BERBASIS PENEMUAN TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN SELF CONCEPT DENGAN MENGONTROL KEMAMPUAN AWAL PESERTA DIDIK KELAS VII SMP - Widayati Widayati; Suyono Suyono; Wardani Rahayu (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
ABSTRACTThis research aims to determine the effect of invention-based learning models on mathematical critical thinking skill and self concept by controlling the initial ability of class VII Junior High School students on the subject of flat building in the academic year 2016/2017. The research method used in this research is quasi experimental method with Posttest Only Control Group Design. The sample in this study amounted to 96 students selected by using cluster random sampling technique with three classes of samples. Methods of data collection in this study were obtained through the provision of initial ability tests, tests of critical thinking skills mathematically, and self concept questionnaires that have been validated and tested its reliability. The data were processed using covariance analysis (ANCOVA) and continued with corrected t-test. The result of the research shows that 1) There is difference of influence of invention-based learning model on mathematical critical thinking skill and self concept by controlling the initial ability of class VII Junior High School students, 2) Mathematical critical thinking skill of learners using guided discovery learning model better than the ability of learners to learn using guided inquiry learning models and conventional learning models, (3) Self Concept mathematical learners who learn by using guided discovery learning model better than learners' ability to learn using guided inquiry model and conventional learning model.Keywords: Invention-Based Learning Model, Mathematical Critical Thinking Skill, Self Concept, Initial Ability